Garlic accelerates red blood cell turnover and splenic erythropoietic gene expression in mice: evidence for erythropoietin-independent erythropoiesis. - Bünyamin Akgül; Kai-Wei Lin; Hui-Mei Ou Yang; Yen-Hui Chen; Tzu-Huan Lu; Chien-Hsiun Chen; Tateki Kikuchi; Yuan-Tsong Chen; Chen-Pei D Tu (PLoS ONE, 2010)
Garlic (Allium sativum) has been valued in many cultures both for its health effects and as a culinary flavor enhancer. Garlic's chemical complexity is widely thought to be the source of its many health benefits, which include, but are not limited to, anti-platelet, procirculatory, anti-inflammatory, anti-apoptotic, neuro-protective, and anti-cancer effects. While a growing body of scientific evidence strongly upholds the herb's broad and potent capacity to influence health, the common mechanisms underlying these diverse effects remain disjointed and relatively poorly understood. We adopted a phenotype-driven approach to investigate the effects of garlic in a mouse model. We examined RBC indices and morphologies, spleen histochemistry, RBC half-lives and gene expression profiles, followed up by qPCR and immunoblot validation. The RBCs of garlic-fed mice register shorter half-lives than the control. But they have normal blood chemistry and RBC indices. Their spleens manifest increased heme oxygenase 1, higher levels of iron and bilirubin, and presumably higher CO, a pleiotropic gasotransmitter. Heat shock genes and those critical for erythropoiesis are elevated in spleens but not in bone marrow. The garlic-fed mice have lower plasma erythropoietin than the controls, however. Chronic exposure to CO of mice on garlic-free diet was sufficient to cause increased RBC indices but again with a lower plasma erythropoietin level than air-treated controls. Furthermore, dietary garlic supplementation and CO treatment showed additive effects on reducing plasma erythropoietin levels in mice. Thus, garlic consumption not only causes increased energy demand from the faster RBC turnover but also increases the production of CO, which in turn stimulates splenic erythropoiesis by an erythropoietin-independent mechanism, thus completing the sequence of feedback regulation for RBC metabolism. Being a pleiotropic gasotransmitter, CO may be a second messenger for garlic's other physiological effects.